The effectiveness of building a proposed guide according to the expansionist theory in developing classroom teaching skills for the practical education course - Uweed Harbi Al Arnoosy, Dihya (International Journal of Psychosocial Rehabilitation, 2020)
Research Summary:The current research aims to define "the effectiveness of building a proposed guide according to the expansionist theory in developing classroom teaching skills for the practical education course."For the purpose of verifying the research goal, the researcher developed the following zero hypotheses:1- There is no statistically significant difference at the level of significance (0.05) between the average scores of students (teachers) in the teaching skills test before and after applying the proposed evidence according to the expansionary theory.2- There is no statistically significant difference at the level of significance (0.05) between the average scores of students (teachers) in the observation card to perform teaching skills before applying the guide.The researcher adopted the descriptive and experimental approaches in preparing and experimenting with the guide and chose the experimental design of one group and the post-achievement test.The current research community was students of Iraqi colleges of education in humanities.The researcher randomly and intentionally selected the fourth graders in the departments of Arabic Language, History, and Geography from the College of Education for Humanities.The researcher performed a statistical equivalence among the sample members in the following variables: degrees of practical education subject.The researcher applied the work in the educational guide, as she printed the guide in the form of a book and distributed it to the sample members on the first day of application (practical education) in schools.The researcher derived (262) behavioral goals covering most levels and areas of behavioral goals.The researcher prepared the teaching skills test to determine the amount of benefit from the educational guide. The test consisted of (36) paragraphs of different types of objective questions and verified the sincerity and reliability of the test and the level of difficulty and strength of its distinction. And the note card, as the second tool for determining the performance level of the sample, consisted of 30 paragraphs, and the researcher verified the validity of the tool and its stability. The researcher used the following statistical methods in the research procedures and reaching the results: monovariance analysis and (T-test) of two interconnected samples, Pearson correlation coefficient, difficulty coefficient equation, paragraph discrimination factor equation, and the effectiveness of error substitutes.After analyzing the data statistically, the researcher reached the following result:The presence of a positive impact on the performance skills of the student with knowledge when applying practical lessons in secondary schools.The researcher came out with a set of conclusions, recommendations, and proposals that complement the current research.Depending on the results of the research, the researcher can conclude the following points:1- The possibility of applying the educational guide several times to samples from the teachers of human majors will achieve good results if it is better applied.2- The educational guide is a close assistant to the teacher or is applied when teaching the subject or at the stage of preparing for the daily lessons.3- The educational guide can be applied by the current teachers during the service and not for the applicants only because the guide is based on the basic needs of teachers in general.4- The educational guide for students in the college can be taught through various educational platforms.In light of the results of the current research, the researcher recommends a set of recommendations, including the following:1- Printing the educational guide and distributing it to the teachers in order to adopt it as an assistant guide for the teachers.2- Directing the students in the last stage of the Iraqi colleges of education to use the educational guide in reaching the appropriate teaching skills for each educational situation that the applied student passes3- Adopting the guide from college professors who are studying practical education as an educational assistant for students and directing their students to seek the help of the educational guide.As a continuation of the current research and in order to develop the educational guide and interest in it, the researcher recommends the following recommendations:1- Conducting a study to design an educational guide for teachers that suits the professional needs of the primary school.2- Conducting a study to design an educational-training manual for the proficiency of the profession for teachers in scientific majors in colleges of education or for English language teachers.3. Conducting a study to design an educational program in the form of an integrated interactive guide that is next to a computerized application in the form of a Windows, Apple, or Android program.